‘Thrilled with Chilly Horror’: A Formulaic Pattern in Gothic Fiction - Aguirre, Manuel (Studia Anglica Posnaniensia, 2015)
There is currently no literature on the topic of formulaic language in Gothic prose fiction. The article resorts to a modified understanding of the term ‘collocation’ as used in lexicography and corpus linguistics to identify the significant co-occurrence of two or more words in proximity. It also draws on insights from the Theory of Oral-Formulaic Composition, in particular as concerns the use of the term ‘formula’ in traditional epic poetry, though again some modifications are required by the nature of Teuthold’s text. The article differentiates between formula as a set of words which appear in invariant or near-invariant collocation more than once, and a formulaic pattern, a rather more complex, open system of collocations involving lexical and other fields. The article isolates a formulaic pattern—that gravitating around the node-word ‘horror’, a key word for the entire Gothic genre –, defines its component elements and structure within the book, and analyses its thematic importance. Key to this analysis are the concepts of overpatterning, ritualization, equivalence and visibility.